Legal Status and Political Representation: The 1986 IRCA and Hispanic Public Officials - Navid Sabet (ZBW - Leibniz Information Centre for Economics, 2020)
What factors lead underrepresented groups to gain more political representation? I digitize a novel source of data that contains records of Hispanics elected to public office from the local to the federal level from 1984 to 1994 and exploit variation in legal status arising from the 1986 Immigration Reform and Control Act (IRCA), which legalized three million Hispanic migrants in the United States, to shed light on this question. I find that counties with more per capita legalized migrants experience significant increases in the number of Hispanics in public office around 1992 when the migrants first gained the right to vote. The result is driven almost entirely by increases at the local level, in particular school board members and mayors of small towns, and is stronger in counties with larger Hispanic populations, pointing to network effects. Individuals in IRCA-affected counties are more politically active, lending credence to the view that the political engagement of the newly legalized helps drive the results. I find no evidence for increased Hispanic candidate entry. Finally, I provide indirect evidence that demand for representation, rather than candidate competence, drives Hispanic selection to public office. Together, the results open a new dimension to the economics of legal status: its effects on political representation.
Keywords: J15; H72; P16; 330; immigrant legalization; identity politics; political representation; franchise extension